MEMBANGUN KESADARAN SOSIAL MELALUI NILAI-NILAI ISLAM UNTUK MENGATASI PERUNDUNGAN DI SMPIT Al-MADINAH KARAWANG - Aftha Ifat Aini; Ramdhani, Khalid; Han Sein, Lau (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying is a social phenomenon that still frequently occurs in educational settings and has a serious impact on the psychological, emotional, and academic development of students. This study aims to analyze the role of Islamic values in fostering social awarenessas a means of preventing bullying at SMPIT Al-Madinah Karawang, as well as to identify the various challenges faced in its implementation. This study employs a qualitative approach using a case study method conducted on May 19, 2025. Data were collected through semi-structured in-depth interviews with the Islamic Religious Education teacher who also serves as the Vice Principal for Curriculum, school activity observations, and documentation. The research results indicate that the integration of Islamic values such as noble character, empathy, discipline, and respect for others is effective in shaping students’ character and reducing bullying behavior through integrated learning programs, religious activities, and a humanistic and communicative approach. However, the main challenges stem from external factors such as the family environment and social circles outside of school, which do not yet fully support the development of students’ character. Therefore, synergy between schools and families is needed through collaborative programs to strengthen the sustained internalization of Islamic values in order to prevent bullying.